DEVELOPMENT OF INTEGRATED SCIENCE E-BOOK WITH A LOCAL WISDOM BASED DISCOVERY LEARNING MODEL FOR SMP/MTs - Firstiana, Annisa (Universe, 2024)
The COVID-19 pandemic period requires the learning process to be carried out online. The observations show the teaching materials used are still limited and are considered not yet able to help students learn independently. Electronic teaching materials are one of the solutions to support the learning process, one of which is electronic books. This study aims to produce an integrated science e-book with a valid and practical discovery learning model based on local wisdom. The type of research used is Research and Development (R&D) with the Plomp development model. This plomp model is limited the one to one stage only. The resulting prototype was tested for validity by three validators, namely the Science Education lecturer, FMIPA UNP. Practicality tests were conducted on two science teachers at SMP Negeri 34 Padang. The instruments used are validity and practicality questionnaires. The results of the validity test obtained average kappa moment value of 0.81 the very high validity category. The results of the practicality test obtained average kappa moment value of 0.86 the very high validity category. Be concluded the integrated science e-book with local wisdom-based discovery learning model for SMP/MTs is valid and practical.